Analytical method of the impact of distributed generation on static voltage stability of distribution network and its development - YANG zhichun (Institute of Advanced Engineering and Science, 2013)
It can’t be ignored that the impact of distribution network to the static voltage stability of the distributed generation. In this paper, we first introduce the stability indices of the traditional grid on static voltage and the analytical method, in the mean time, we put forward the corresponding advantages and disadvantages and applicable scope. Then, we present a summary of the current research on the impact of distribution network to the static voltage stability of the distributed generation at home and abroad from the two aspects of the static voltage stability indices and analytical methods. In the end, the paper points out a new way to improve the distribution network static voltage stability that with the consistency theory to achieve coordinated control of distributed generation, microgrid, as well as virtual power plants, which will be more advantage. This article has a reference value for the analysis of the impact of distributed generation on static voltage stability of the distribution network, as well as researches the measures to improve the static stability. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.2255